Interest of black carob extract for the development of active biopolymer films for cheese preservation. (April 2021) - Pérez, María Jorgelina; Moreno, María Alejandra; Martínez-Abad, Antonio; Cattaneo, Florencia; Zampini, Catiana; Isla, María Inés; López-Rubio, Amparo; Fabra, María José
A b s t r a c t: The aim of this work was to develop bio-based packaging materials based on black carob extracts (BCE) and κ-carrageenan (κ-c) blends, and to study their impact for cheese preservation. Firstly, black carob extracts were obtained with and without alcohol pre-treatment (BCE-a and BCE-b), respectively, and its chemical composition and antioxidant properties was analysed. Protein and polyphenol contents were higher in the extract without alcohol pre-treatment (BCE-b). Different bio-based films were prepared by mixing BCEs with κ-c at different ratios, and the morphological, thermal, mechanical and water barrier properties of the films were evaluated. The antioxidant efficacy of BCE:κ−c films prepared with both BCE extracts was further compared when applied on the preservation of cheese slides. Results showed that skipping the ethanolic extraction pre-treatment gave rise to more ductile films due to the presence of sucrose and other small sugars or the higher protein content in the BCE-b extract, which could have a plasticizer effect on the biopolymer network. Mixtures with κ−c increased the rigidity of the films. A good correlation between barrier properties of films and the antioxidant efficacy on cheese samples was observed, suggesting that not only the antioxidant properties but also the physicochemical properties of the films had a direct impact on cheese quality and preservation. Films prepared with both BCEs at 50:50 BCE:κ−c ratio and those prepared with BCE-a at 25:75 BCE:κ−c ratio, presented good antioxidant capacity and a good compromise for physicochemical properties. However, from the economical point of view, 50:50 BCE-b:κ−c films are more suitable since the extraction protocol of BCE-b was simpler and the yield was three-fold higher. Graphical abstract: Image 1 Highlights : Black carob extracts (BCE) and κ-carrageenan (k-c) active films were developed. Black carob extracts were obtained with and without alcohol pre-treatment. Protein and polyphenol contents were higher in the extract without alcohol pre-treatment. Films prepared with 50:50 BCE:κ-c ratio showed very promising properties. The developed active films successfully improved cheese preservation.